2019
DOI: 10.1186/s12964-019-0334-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet-activating factor-induced interleukin-8 expression by protein tyrosine phosphatase 1B

Abstract: Background Platelet-activating factor (PAF) is a potent lipid mediator whose involvement in the onset and progression of atherosclerosis is mediated by, among others, the modulation of cytokine expression patterns. The presence of multiple potential protein-tyrosine phosphatase (PTP) 1B substrates in PAF receptor signaling pathways brought us to investigate its involvement in PAF-induced cytokine expression in monocyte-derived dendritic cells (Mo-DCs) and to study the pathways involved in this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…Further, MAPK-phosphorylated Thr188 may act as a priming site for GSK3β-mediated phosphorylation of Ser184 and Ser179, i.e., phospho-residues favoring dimerization due to conformational changes and enhancing both DNA binding and transactivation activity [40,258]. Decreased C/EBPβ-Thr235 phosphorylation due to GSK3 inactivation was detected in TNF long-term-incubated monocytic cells in the presence of kenpaullone [259] as well as human monocyte-derived DC in response to platelet-activating factor [260]. In contrast, in IL-17-stimulated murine ST2 stromal cells, ERK-mediated priming phosphorylation at Thr188 and subsequent phosphorylation at Ser179 by GSK3 have been described as being repressive for certain C/EBP-dependent genes [261].…”
Section: C/ebp-associated Signalingmentioning
confidence: 96%
“…Further, MAPK-phosphorylated Thr188 may act as a priming site for GSK3β-mediated phosphorylation of Ser184 and Ser179, i.e., phospho-residues favoring dimerization due to conformational changes and enhancing both DNA binding and transactivation activity [40,258]. Decreased C/EBPβ-Thr235 phosphorylation due to GSK3 inactivation was detected in TNF long-term-incubated monocytic cells in the presence of kenpaullone [259] as well as human monocyte-derived DC in response to platelet-activating factor [260]. In contrast, in IL-17-stimulated murine ST2 stromal cells, ERK-mediated priming phosphorylation at Thr188 and subsequent phosphorylation at Ser179 by GSK3 have been described as being repressive for certain C/EBP-dependent genes [261].…”
Section: C/ebp-associated Signalingmentioning
confidence: 96%
“…Infection of cells by human rhinovirus, HRSV, coronavirus, or influenza A virus is known to increase the PAFR expression level and enhance the adhesion of Staphylococcus aureus , S. pneumoniae , and H. influenzae to lower respiratory epithelial cells ( Avadhanula et al, 2006 ; Hendaus et al, 2015 ). Previous work has shown that PAFR expression is induced by several inflammatory factors, including interleukins-1 and -6 and tumor-necrosis factor alpha, resulting in increases in the levels of both normal cell surface-displayed and PAFR ( Ishizuka et al, 2003 ; Garcia et al, 2010 ; Hamel-Côté et al, 2019 ). These reports suggested that regulation of bacterial adhesion-related cellular receptors is associated with the severity of pneumoniae ( Wang et al, 2009 ; Sacco et al, 2014 ; Hendaus et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kinases and phospholipases whose activation is induced by PAF include MAPK, protein kinase C (PKC), phosphatidylinositol 3-kinase (PI3K), protein tyrosine kinases, G-protein-coupled receptor kinase, and multiple intracellular signal transducers (Ishii and Shimizu, 2000 ). In addition, PAF regulates the expressions of interleukin (IL)-1, IL-6, IL-8, and pleiotropic cytokines (Hamel-Côté et al, 2019a , b ). As an inflammatory factor, PAF plays an important role in many pathological conditions.…”
Section: Chemical and Pharmacological Characteristics Of Ginkgolidesmentioning
confidence: 99%